Increased positive affect is associated with less generalization of pain-related avoidance. (November 2022) - Vandael, Kristof; Meulders, Michel; Mühlen, Katharina zur; Peters, Madelon; Meulders, Ann
Abstract: Fear-avoidance models of chronic pain consider excessive spreading (or overgeneralization) of pain-related avoidance toward safe activities to play a crucial role in chronic pain disability. This study ( N  = 96) investigated whether avoidance generalization is mitigated by positive affect induction. Pain-free, healthy participants performed an arm-reaching task during which certain movements were followed by pain, while another was not. One group then performed an exercise to induce positive affect (positive affect group), while another group performed a neutral exercise (neutral group). A third group also performed the neutral exercise, but did not learn to avoid pain during the arm-reaching task (yoked neutral group). To test generalization, we introduced novel but similar movements that were never followed by pain in all groups. Results showed no differences in generalization between the positive affect and neutral groups; however, across groups, higher increases in positive affect were associated with less generalization of avoidance, and less generalization of pain-expectancy and pain-related fear. Compared to the yoked neutral group, the neutral group showed avoidance generalization, as well as pain-expectancy and pain-related fear generalization. These results point toward the potential of positive affect interventions in attenuating maladaptive spreading of pain-related avoidance behavior to safe activities. Highlights: Increased positive affect was associated with less avoidance generalization. Increased positive affect was associated with less fear/expectancy generalization. Previous findings regarding generalization of costly avoidance were replicated. Results highlight the potential of mood induction in safety learning.